GERAKAN IMPRESIONISME, DEBUSSY DAN “CLAIR DE LUNE”: SEBUAH REFLEKSI TERHADAP PERUBAHAN - Daniel Sema (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2018)
Impressionism derives its source of inspiration from external, even exotic sources; its literature, art and music are easily projected outside; the recipient of its colorful images has the means of comparing photoreality with the artist’s experience of it. This impressionism movement starts from painting, then penetrated into other arts fields. Impressionism has changed the way people view art. It has been considered the setting stone of Modern Art. In general, impressionism has changed the perspective of art, itself.